An ethnomusicological perspective on the musical identity of the city: Male henna nights in Elazığ - İlhan, Serap Yağmur (Nilgun SAZAK, 2026)
In this study, it is aimed to examine male henna night traditions in Elazığ, focusing on their musical performance practices, ritual structures, and other cultural characteristics. In this respect, the study is significant for its contribution to the literature at both local and national levels from an ethnomusicological perspective. The research is structured within the framework of qualitative methodology and designed according to a ethnographic research model. In this sense, interviews were conducted with nine individuals who had witnessed this tradition between 1960 and 1980 and who were professionally or amateurly involved in music and/or folk dance. The reason for selecting individuals who had witnessed the henna night tradition during the specified years is that this period represents the most vibrant and prominent era of the tradition. Based on the data obtained from the interviews, a musical transcription of a piece performed during Elazığ male henna nights was prapared. Furthermore, the researcher participated in a contemporary henna night that is currently being performed in an attempt to preserve its authenticity in Elazığ, and particular observations were conducted. The findings indicate that Elazığ male henna nights consist of a combination of numerous rituals taking place before, during, and after the henna ceremony. The presence of music as an inevitable element in each of these rituals demonstrates that male henna nights have acquired a character unique to Elazığ in both musical and ritual terms. This study reveals notable results showing that Harput Music and local folk dances specific to Elazığ dominate the instruments and musical repertoire performed during male henna nights. Moreover, the relationships between space and music, as well as culture, music, and religion, play a significant role in these cultural events. In addition, it was concluded that male henna nights in this region differ from female henna nights in many aspects, including the instruments used, performance practices, the gender of the musicians, and the repertoire. As the relevant literature is scrutinized, it shows that although male henna nights are mentioned within various contexts, they have not been examined comprehensively, particularly in terms of their musical-ritual structures and other cultural characteristics. In this respect, henna nights were examined through a holistic approach by comparing their past and present practices. From this perspective, the study represents the first comprehensive research on this subject. Copyright © 2026 The Author(s). This is an open access article distributed under the Creative Commons Attribution License (CC BY), which permits unrestricted use, distribution, and reproduction in any medium or format, provided the original work is properly cited.
Şehrin müzikal kimliğine etnomüzikolojik bir bakış: Elazığ’da erkek kına geceleri
Keywords: culture; Elazığ; Elazığ Harput; erkek kına gecesi; ethnomusicology; etnomüzikoloji; Harput; Harput Music; Harput Musikisi; kültür; men’s henna night; musicocultural structure; müzikokültürel yapı